Studie proveditelnosti výstavby a zprovoznění minipivovaru - Hejlová, Ludmila; Ludmila Hejlová (České vysoké učení technické v Praze, 2021)
Diplomová práce se zabývá studií proveditelnosti výstavby a zprovoznění minipivovaru v obci Horní Čermná. Teoretická část zahrnuje popis projektu a jednotlivých částí studie proveditelnosti. Praktická část je zaměřena na analýzu vnějšího pro-středí společnosti, kalkulaci ceny, nákladů a tržeb. Dále obsahuje předběžné lidské a materiální zdroje, implementaci a ekonomické vyhodnocení celého projektu.

The goal of diploma thesis is creating feasibility study of the construction and commissioning of a mini-brewery in the village Horní Čermná. The theoretical part includes a description of the project and individual parts of the feasibility study. The practical part is focused on the analysis of the external environment of the company, the calculation of prices, costs and sales. It also contains preliminary human and material resources, implementation and economic evaluation of the whole project.
Feasibility Study of Construction and Commissioning of a Minibrewery
Keywords: Studie proveditelnosti; projekt; projektové řízení; doba návratnosti; analýza rizik; minipivovar; Feasibility study; project; project management; payback period; risk analysis; mini-brewery